Nursing in the new millenium - Shakya, Nandika (Journal of Institute of Medicine Nepal, 2001)
This article addresses the fast changing trends in nursing education and practice in Nepal, which is the result of economic situation of the country, the changing technology and demography, and the knowledge explosion. The shifting nursing paradigm of the world also is considered here in order to run educational and health care institution effectively in the modern world. The WHO Expert Committee’s advice on innovative curriculum planning and adapting teaching and learning methodology are some important facts stated here for shaping the profession according to the need of the society. The changing trends in nursing curriculum, and the strategies essential to undertake before reviewing nursing curriculum are pointed out to guide the nurse practitioners as well as the educationists